Determination of the complete covalent structure of the major glycoform of DQH sperm surface protein, a novel trypsin-resistant boar seminal plasma O-glycoprotein related to pB1 protein - Bezouska, K; Sklenár, J; Novák, P; Halada, P; Havlícek, V; Kraus, M; Tichá, M; Jonáková, V (Protein science, 1999)
The complete covalent structure of a novel boar DQH sperm surface protein resistant to many classical procedures of enzymatic fragmentation was determined. The relative molecular mass of the major form of this protein determined by ESI-MS and MALDI-MS was 13,065.2+/-1.0 and 13,065.1, respectively. However, additional peaks differing by 162 Da (i.e., minus hexose), 365 Da (i.e., minus hexose and N-acetylhexosamine), 146 Da (i.e., plus deoxyhexose), and 291 Da (i.e., plus sialic acid) indicated the heterogeneity due to differences in glycosylation. The complete covalent structure of the protein was determined using automated Edman degradation, MALDI-MS, and post-source decay (PSD) MALDI-MS, and shown to consist of N-terminal O-glycosylated peptide followed by two fibronectin type II repeats. The carbohydrates are O-glycosidically linked to threonine 10, as confirmed by PSD MALDI-MS of the isolated N-terminal glycopeptide. Eight cysteine residues of the protein form four disulfide bridges, the positions of which were assigned from MALDI-MS and Edman degradation data. We conclude that mass spectral techniques provide an indispensable tool for the detailed analysis of the covalent structure of proteins, especially those that are refractory to standard approaches of protein chemistry.
Keywords: glykoproteiny; Animals; transportní proteiny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Glycosylation; sekvence aminokyselin; Membrane Glycoproteins; Molecular Sequence Data; prasata; Glycoproteins; Amino Acid Sequence; Carrier Proteins; molekulární sekvence - údaje; molekulová hmotnost; Protein Conformation; Male; Swine; glykosylace; konformace proteinů; spektrometrie hmotnostní - ionizace laserem za účasti matrice; membránové glykoproteiny; zvířata; mužské pohlaví; Molecular Weight